THE EFFECT OF PRODUCT QUALITY AND PRICE ON SKINTIFIC SKINCARE PURCHASE DECISIONS IN MEDAN CITY - Ida Royani; Riyandhi; Nur Hafni; Maisyura; Lisa Iryani (RADJA PUBLIKA, 2024)
This study aims to determine the effect of product quality and price on purchasing decisions for Skintific skincare. This study uses descriptive quantitative research explaining that this method is based on the philosophy of positivism, used in examining samples and research populations using Non-Probability Sampling with Convenience Sampling techniques. The research population is people in Medan City who use or have used Skintific skincare products. This sample was obtained as many as 96 respondents. Data was collected using a questionnaire. The data analysis used in this study used multiple linear regression with the help of the SPSS 26.0 software program. Partial hypothesis testing shows that the product quality variable has a positive and significant effect on purchasing decisions with a sig value. 0.000 <0.05 and the tcount value is 3.621> t table 1.986. Then for the price variable, it has a positive and significant effect on purchasing decisions with sig. 0.005 <0.05 and the t count value is 2.870> t table 1.986. While simultaneously showing that product quality and price both have a positive and significant effect on purchasing decisions with a sig value. 0.000 <0.05 and the value of fcount 39.022> ftable 3.09.